2016
DOI: 10.1152/physrev.00026.2015
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aldosteronism: Changing Definitions and New Concepts of Physiology and Pathophysiology Both Inside and Outside the Kidney

Abstract: In the 60 years that have passed since the discovery of the mineralocorticoid hormone aldosterone, much has been learned about its synthesis (both adrenal and extraadrenal), regulation (by renin-angiotensin II, potassium, adrenocorticotrophin, and other factors), and effects (on both epithelial and nonepithelial tissues). Once thought to be rare, primary aldosteronism (PA, in which aldosterone secretion by the adrenal is excessive and autonomous of its principal regulator, angiotensin II) is now known to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
137
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 589 publications
(754 reference statements)
2
137
0
2
Order By: Relevance
“…The low rates of diagnosis are also observed in GP clinics throughout Victoria, ranging from 0.1% to 0.45% of patients with hypertension (survey of ten GP clinics in Victoria, unpublished data). Although a younger age of onset of hypertension and associated hypokalaemia may prompt the clinician to consider a diagnosis of PA, both our clinical experience and previous studies have shown that the average age of onset of PA is 40–50 years and hypokalaemia is only present in 9–37% of patients 4 . Hence, age and potassium levels are not reliable clinical markers of PA.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The low rates of diagnosis are also observed in GP clinics throughout Victoria, ranging from 0.1% to 0.45% of patients with hypertension (survey of ten GP clinics in Victoria, unpublished data). Although a younger age of onset of hypertension and associated hypokalaemia may prompt the clinician to consider a diagnosis of PA, both our clinical experience and previous studies have shown that the average age of onset of PA is 40–50 years and hypokalaemia is only present in 9–37% of patients 4 . Hence, age and potassium levels are not reliable clinical markers of PA.…”
mentioning
confidence: 80%
“…Undiagnosed PA leads to poor BP control and increased cardiovascular, renal and metabolic morbidity and mortality related specifically to the effect of aldosterone excess mediated by the mineralocorticoid receptor 4 . Several research groups have independently shown the detrimental impact of mineralocorticoid receptor activation on cardiac inflammation and fibrosis in animal models 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] The excess aldosterone production that causes the disorder may be unilateral (confined to one adrenal) or bilateral and the 2 forms are preferentially treated by unilateral adrenalectomy or a mineralocorticoid receptor antagonist, respectively. 6,7 Unilateral PA is the most common surgically September 2018 correctable cause of hypertension with a highly variable proportion of patients achieving clinical remission after surgery between centers. [8][9][10] Patients with PA have a widely reported increased risk of prevalent cardiovascular and cerebrovascular complications and target organ damage relative to matched patients with primary hypertension who have otherwise similar cardiovascular risk profiles or compared with the general population with hypertension.…”
mentioning
confidence: 99%
“…The diagnosis is mainly clinical with subsequent identification of the causal mutation, that however, is not obtained in all cases, indicating that as yet unidentified genes are associated with this condition [24]. To date, mutations of 4 genes have been described: mutations in WNK1 and WNK4 kinases [25], and more recently KLHL3 and CUL3 mutations [26].…”
Section: Monogenic Forms Of Hypertensionmentioning
confidence: 99%